Recent advances and prospects in polymeric nanofluids application for enhanced oil recovery - Gbadamosi, A.O. (Korean Society of Industrial Engineering Chemistry, 2018)
Enhanced-oil-recovery (EOR) processes are used to recover bypassed and residual oil trapped in the reservoir after primary and secondary recovery methods. Recently, novel materials formed from incorporation of polymer and nanoparticles have gained attention and are proposed for EOR applications due to their fascinating properties. Herein, we review the recent advances and prospects of the application these polymeric nanofluids in crucial aspects of EOR such as stability and adsorption, wettability alteration, interfacial tension reduction and emulsion stability, and rheology. The mechanisms of their improved efficiency were elucidated, gaps in the research were highlighted, and recommendation for future works were outlined. Â© 2018 The Korean Society of Industrial and Engineering Chemistry